Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta psychologica, 2006)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184–197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation with temporal-order judgments may induce a methodological problem resulting in fairly low estimates. A method which provides a more exhaustive measure is suggested and tested.